Obtaining of nectarinum (Prunus persica (L.) Batsch subsp. nectarina (Ait.) Shof.) polyploid plants in Nikitsky Botanical Gardens - Є. П. Шоферістов (Plant Varieties Studying and Protection)
Firstly in Ukraine as the result of resiprocal interbreedings of autotetraploid (2n=4x=32) / diploid (2n=2x=16) and diploid (2n=2x=16) / autotetraploid (2n=4x=32) four sintetic triploid (2n=3x=24) hybrid forms (611-91, 13-93, 14-93, 18-93) have been obtained. Spontaneous triploid nectarinum 166-80 has been shared out from diploid hybrid seedlings population. Tetraploid and triploid nectarinum forms are valuable sources for directoinal selection and making hybrids with the complex of new signs, which are difficult or impossible to receive on diploid level.